Infant Feeding Advice and Sustainable Alternatives in Low-Income South African Contexts - Seeletse, Selogile Philda; Nganase, Tebogo; Moremi, Dikeledi; Ndobe, Tsakani Violet; Seeletse, Solly Matshonisa (Journal of Cultural Analysis and Social Change, 2026)
The study aimed to determine the lived experiences of mothers and caregivers (M/Cs) from low-to no income families, who are coerced to feed their infants formulas prescribed by health professionals against thin soft-porridge, and to understand the old ways of preparing the soft porridge for babies. Two samples of M/Cs and elderly mothers (elders) were used from accidental sampling and purposive sampling for this aim, with data collection done by interviewing them. Thematic content analysis was used for analysing the interview transcripts. The M/Cs find it difficult to cope with high formula prices, and they find it causing them psychological challenges such as anxiety, depression, and financial stress. The elders decried the marginalization of indigenous knowledges (IKs) where child and baby feeding were also included. A hybrid model that blends modern ways and IKs are integrated for use in infant feeding, without imposing or restricting any one of the methods.